From Little Things Big Things Grow: Australia’s Evolving Site Blocking Regime - Foong, Cheryl; Gray, Joanne (Thomson Reuters, 2020)
Australia's website-blocking regime, introduced in 2015 and expanded in 2018, permits injunctions requiring internet service and search engine providers to block access to overseas websites that have the "primary effect" or "primary purpose" of facilitating copyright infringement. Furthermore, the injunction may be "adaptive" in nature – rightsholders may by agreement with internet service or search engine providers extend the injunction to apply to mirror locations online, without returning to court. In this article, we critically analyse the trajectory of this so-called "no fault" enforcement regime, and highlight the lack of transparency fostered by the regime. We challenge the conception of the regime as a form of proprietary protection and the resulting uncritical reliance by lawmakers on private ordering as a keystone of online copyright enforcement. Finally, we provide recommendations for addressing the flaws in the current design of Australia's copyright site-blocking regime.